Effectiveness of Assessment for Learning Instruments in Project-based Physics Learning to Measure Collaboration and Problem-Solving Skills - Dwinda, Syahnaz Gustianne; Rosidin, Undang; Herlina, Kartini (Universitas Syiah Kuala, 2024)
In general, the assessment model used by teachers in teaching only revolves around summative assessment, thus students cannot use it to identify the strengths and weaknesses of their skills in learning activities. This study aims to determine the effectiveness of the Assessment for Learning instrument in project-based physics learning to measure collaboration and problem-solving skills. The research design utilizes a pretest-posttest control group design. The population for this study includes all second-semester eleventh-grade science students, with the sample comprising eleventh-grade science 3 as the experimental group and eleventh-grade science 4 as the control group selected through random sampling technique. The instruments used include the Assessment for Learning learning assessment instrument and assessment to evaluate and improve students' collaboration and problem-solving activities. Data collection techniques involve observation and questionnaire collection. Data are analyzed using descriptive statistical data analysis and inferential statistics. The hypothesis testing results of collaboration and problem-solving skills indicate differences in collaboration and problem-solving skills between the experimental and control classes in project-based physics learning. It is concluded that assessment using AfL in project-based physics learning is effective in measuring collaboration and problem-solving abilities as it exceeds classical mastery.